2021
DOI: 10.1111/gcb.15798
|View full text |Cite
|
Sign up to set email alerts
|

A Gulf in lockdown: How an enforced ban on recreational vessels increased dolphin and fish communication ranges

Abstract: From midnight of 26 March 2020, New Zealand became one of the first countries to enter a strict lockdown to combat the spread of COVID‐19. The lockdown banned all non‐essential services and travel both on land and sea. Overnight, the country's busiest coastal waterway, the Hauraki Gulf Marine Park, became devoid of almost all recreational and non‐essential commercial vessels. An almost instant change in the marine soundscape ensued, with ambient sound levels in busy channels dropping nearly threefold the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The COVID-19 pandemic presents a remarkable opportunity for both management and research (Rutz et al, 2020), and has provided marine life with short-term relief from some anthropogenic impacts (Pine et al, 2021). With the future of cruise ship and wildlife tourism in flux, we have a renewed opportunity to address and improve sustainability of these industries worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic presents a remarkable opportunity for both management and research (Rutz et al, 2020), and has provided marine life with short-term relief from some anthropogenic impacts (Pine et al, 2021). With the future of cruise ship and wildlife tourism in flux, we have a renewed opportunity to address and improve sustainability of these industries worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient sound in the ocean is thought to have increased 3 dB per decade (Hildebrand, 2009): the same magnitude as the sound decrease reported in some of these articles over a few months' time. Studies published in other journals have also found reductions in sound levels due to the pandemic (Thomson and Barclay, 2020;León-López et al, 2021;Pine et al, 2021).…”
Section: Summary Of Covid-19 Papersmentioning
confidence: 94%
“…If the observer knows a target species' signal characteristics, these sounds may be more easily detected, but without prior knowledge of either presence or structure of sounds, listening through the noise can be difficult. This has been highlighted by the recent COVID "anthropause" experienced at various aquatic locations around the world (e.g., Bates et al, 2021;De Clippele and Risch, 2021;Dunn et al, 2021;Gabriele et al, 2021;Ryan et al, 2021), where removal of the anthropogenic component of some soundscapes has provided an opportunity to observe sounds (and therefore presence) of marine fauna that might otherwise be lost in the noise (e.g., Pine et al, 2021). However, it is not just anthropogenic noise that limits acoustic detection of marine fauna.…”
Section: Environmental Noisementioning
confidence: 99%